Pomegranate cultivation is promising in arid region of Rajasthan - Meena, Nirmal Kumar; Asrey, Ram; Baghel, Murlimanohar (Indian Farming, 2018)
The present article sums up the prospect of pomegranate in Thardesert. Because of its low cost inputs and high nutritional value, demand of pomegranate has been increased tremendously. Integration of pomegranate cultivation into existing farming system in such undulated and less fertile areas could bring high return and better productivity. It could be a viable option for poorÂ  farmers for getting livelihood and nutritional security.